Hormones, Metabolism and the Benefits of Exercise - Spiegelman, Bruce (Research and Perspectives in Endocrine Interactions, 2018)
metabolic diseases; obesity; type 2 diabetes; muscle glycogen; skeletal muscle microRNAs; Tryptophan-kynurenine metabolites; FNDC5/irisin; AMPK; human brown adipose tissue plasticity